Black Women’s Journey in America and the Need for Intersectionality - Damas, Ana Rafaela (2023)
Through a comparative reading of Maya Angelou’s “Still I Rise”, Lucille Clifton’s “won’t you celebrate with me” and June Jordan’s “Poem About My Rights”, this essay aims to analyse the black women’s journey in America, by considering their identity and the adversities they faced during their path under the light of Kimberlé Crenshaw’s concept of “intersectionality”.